Artificial crime analysis systems using computer simulations and geographic information systems - Liu, Lin, 1965-; Eck, John.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book discusses leading research on the use of computer simulation of crime patterns to reveal hidden processes of urban crimes, taking an interdisciplinary approach by combining criminology, computer simulation, and geographic information systems into one comprehensive resource"--Provided by publisher.
Section V. Conclusion -- Chapter XX. Varieties of artificial crime analysis: purpose, structure, and evidence in crime simulations / John Eck and Lin Liu -- Compilation of references -- About the contributors -- Index.
Includes bibliographical references (p. 433-466) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 25, 2010).
Keywords: Crime analysis -- Data processing; Criminology -- Computer network resources; Digital mapping; Information storage and retrieval systems -- Law enforcement; Geographic information systems; Agent-based simulation research; Artificial intelligence agents; Cellular automata; Crime event and pattern simulations; Geographic information systems tools; Microscopic simulation; Nature of crime; Role of simulation in crime research; Simulation methods; Social networks; Software techniques; Space-time measures of crime diffusion; Street crimes rates and statistics; Streets, networks, and crime distribution; Swarm intelligence; Urban landuse; Validity in simulation; Visualization methods; Electronic books